ANALISIS KEPUASAN PASIEN TERHADAP LAYANAN ADMISSION DI PUSKESMAS TANJUNG BINGKUNG KABUPATEN SOLOK TAHUN 2025 - Arif Prima; Satrio Bhagas Yudhanto; Siti Handam Dewi; Aulia Rahmi Cheni; Nia Watri Wahyuni (Ensiklopedia Education Review, 2025)
Admission services represent the initial point of contact between patients and healthcare facilities and play a crucial role in shaping patients’ perceptions of healthcare service quality. This study aimed to analyze patient satisfaction with admission services at Puskesmas Tanjung Bingkung, Solok Regency, during September 2025. The study employed a descriptive quantitative method with a cross-sectional design. The research population consisted of 1,723 outpatient visits, with a sample of 95 respondents determined using the Slovin formula and selected through accidental sampling. Data were collected using a questionnaire based on the five Servqual dimensions, measured on a Likert scale ranging from 1 to 5. The results indicated varying levels of patient satisfaction across dimensions: Tangible (74%, satisfied), Reliability (68%, satisfied), Responsiveness (55%, moderately satisfied), Assurance (82%, satisfied), and Empathy (79%, satisfied). The study concluded that while staff competence and professionalism (Assurance) demonstrated the highest satisfaction level, service speed (Responsiveness) remains a critical issue due to high patient volume. Therefore, the implementation of a digital queue management system is recommended to enhance the efficiency of admission services at Puskesmas.Keywords : patient satisfaction, admission services, Servqual, Puskesmas